Colombian class action and social rule of law: A propósito de un estudio de caso - Tovar Mg, Luis Freddyur (2018)
This document shows the result of two and a half years of work of the members of the Observatory of judicial activity of the Group of Public Interest Law –POLITES– attached to the research group IJUD of the Law School of Pontificia Universidad Javeriana Cali, about the effectiveness of judicial protection of collective rights and interests protected by the Class actions, processed in the period 2004-2013 in the Administrative Tribunal of Valle del Cauca. This work then relates the seven (7) categories of study mentioned below: claimants, defendants, collective rights threatened, terms, covenant compliance, economic incentives and legal decision; for this purpose, the guide question was: Does the legal proceedings of a lawsuit class action meets the constitutional purposes devised by the constituent of effective protection of collective rights? The text is developed in two parts: a theoretical part, where the concept of rule of law and transition to constitutional and democratic state of law is analyzed, through the rule of law; and the second, a practical part, in which the result of field research conducted in the first instance judicial body is reflected.